PIGMENTARY UVEITIS ASSOCIATED WITH IRIDOCILIARY CYSTS IN AMERICAN BULLDOGS - Pereira, Jorge da Silva; Giannico, Amália Turner; Rincón, Eva Martínez; Villagrasa-Hijar, Manuel; Giannico, Amália Turner; Montiani-Ferreira, Fabiano (Archives of Veterinary Science, 2014)
Presence of iridociliary cysts may cause a specific form of uveitis not associated with any known systemic disease or underlying cause. The condition was previously characterized in golden retrievers. However, Labrador retrievers, Great Danes and Boston terriers are reported to develop a similar disease condition. The following report documents seven cases of iridociliary cysts, with or without associated pigmentary uveitis, in American bulldogs from Brazil and Spain. Although not an uncommon disease, this syndrome has been relatively infrequently documented in the literature, with only one study in the American bulldog. This article describes clinical findings as well as medical and surgical management of each case. Because some of the patients were closely related in this series, a possible hereditary basis is considered for pigmentary uveitis associated with iridociliary cysts in American bulldogs.